Endoscopic treatment for hepaticojejunostomy anastomotic stricture: Advantages and disadvantages of balloon dilatation with stenting. Issue 3 (29th September 2021) - Kuwatani, Masaki; Sakamoto, Naoya
Abstract : This Editorial refers to the article by T. Tomoda et al., p 604‐611 of this issue.